2007
DOI: 10.1038/sj.onc.1210895
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes are marked by histone 3 lysine 9 trimethylation in human cancer cells

Abstract: Histone H3 lysine 9 trimethylation (H3K9Me3) has been associated with transcriptional repression, but recent findings implicate this chromatin modification in transcriptional activation and mRNA elongation by RNA polymerase II. Here, we applied immunoprecipitation (IP) with a custom DNA tiling microarray containing many transcription factors important in development and cancer (for example homeotic genes; N ¼ 683 total genes) to explore the relationship between H3K9Me3 and other histone modifications with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 41 publications
11
59
0
Order By: Relevance
“…H3K9me3 is previously thought to be a repressive epigenetic mark (Eissenberg and Shilatifard 2006). Recent studies suggest, however, that H3K9me3 could activate gene expression (Wiencke et al 2008). In contrast to epigenetic marks, there was no significant difference in the proportion of small RNA or microRNA target genes among cis, trans, and background genes (Table S4).…”
Section: Resultsmentioning
confidence: 49%
“…H3K9me3 is previously thought to be a repressive epigenetic mark (Eissenberg and Shilatifard 2006). Recent studies suggest, however, that H3K9me3 could activate gene expression (Wiencke et al 2008). In contrast to epigenetic marks, there was no significant difference in the proportion of small RNA or microRNA target genes among cis, trans, and background genes (Table S4).…”
Section: Resultsmentioning
confidence: 49%
“…This and histone H3 lysine 4 trimethylation (H3K4me3) are enriched at actively transcribed genes (Bernstein et al, 2005;Wiencke et al, 2007). Similarly, the relationships between histone acetylation and gene transcriptional activation by rendering chromatin accessible to the transcriptional machinery are widely recognized (Bernstein et al, 2007;Esteller, 2008).…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…S5), we found that it is enriched in the H3K9me3 histone mark. This chromatin mark has been associated with transcriptional repression but was also found in the promoters of transcriptionally active genes (43). The functional roles of H3K9me3 in the accessible chromatin have not been established, and it is not clear whether H3K9me3 is a normal counterpart in the transcription of all genes or whether it is aberrant readout of the histone code in cancer cells (43,44).…”
Section: St3-h2a2mentioning
confidence: 99%